Urological problems of gynecological surgery. Results obtained with ureterocistoneostomía - Arenas, Normando (2015)
Brief remarks about behavior are made to follow in surgical injuries of the ureter, both discovered during the operation as fistulas which then appear as late complications. In the latter we are in favor of ureteral implantation into the bladder and if the injury is high draw on the proposed operation by Boari. Hydronephrosis is not a contraindication to the ureter-neocistostomía, as Hans Muth observations and our show a trend of hydronephrosis to yield, after a successful deployment. Two clinical histories of uretero-vaginal fistulas healed by neo implementation, with each technique and the other Laztko Boari are then summarized and followed in its evolution by successive excretory pyelograms.